Determination of selected heavy metals concentrations in water spinach (Ipomea aquatica sp.) / Nursyamimi Zulkurnain - Zulkurnain, Nursyamimi (2019)
Vegetables are essential in human diet but unfortunately it may also contribute to heavy metals consumption. Heavy metals in vegetables are related with direct and indirect adverse health effects. This study determined the selected of heavy metals concentration (Mn, Cu, Zn and Pb) for leaves and stem part in water spinach (Ipomea Aquatica) that taken from different sources around Jengka and UiTM area. The aim for this study was to estimate the health risk assessment of heavy metals in water spinach to human health and to compare the heavy metal concentration with the permissible limit value stated by WHO/FAO. The concentrations of heavy metal were analyzed using Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES). The results showed that the water spinach sample from source A (leaves) were higher in manganese which is 9.41 mg/kg rather than other studied metals and it has exceed the permissible limit value by WHO. All of the water spinach samples for leaves and stem part showed no hazard level since the HQ values were less than 1. All tested samples for water spinach were safe to be consumed and did not pose any risk to human health because the HQ values are lower.